Using Ergonomics Based Instruction in Teaching English Language Integrated Skills - Rasha Said; Maha El-Bayaa; Walaa El-Henawy; Jehan El Bassuony (Port Said Journal of Educational Research)
Ergonomics is a multidisciplinary scientific discipline that studies man-artifact interaction. Ergonomics-tailored teaching and learning materials and activities require to consider jointly the needs of the users (i.e. teachers and students) and the resources within the learning environment. The fundamental question confronting educational ergonomics is how to incorporate ergonomics into interventions targeting designing features in the learning environment to improve the learning performance of EFL students, particularly English language integrated skills. This paper, therefore, sets out to show how ergonomics features that consider users’ factors and reduce discomfort can be utilized in teaching the English language. It addresses the following points: the definition of ergonomics based-instruction, the importance of using ergonomics in EFL education, and how teachers can incorporate ergonomics in teaching the English language integrated skills. Finally, the researchers provide conclusions and pedagogical implications as well as suggestions for future research agenda regarding adopting an ergonomics perspective in EFL education and fostering ergonomics literacy.